ИССЛЕДОВАНИЕ СКВАЖИН НОВЫХ МЕСТОРОЖДЕНИЙ МАНАВСКОЙ НЕФТИ (World Science, 2018)
An investigation of oils from new wells of Manavi oil deposit was carried out. Physical and chemical and geochemical parameters, as well as functional groups were determined by IR spectrometry. Using simulative chromatographic distillation of oil from the #12 well naphtha 35-180 °C and diesel fractions were obtained. Individual paraffinic, naphthenic and aromatic hydrocarbons were identified in naphtha by gas chromatographic method and distribution of individual n-paraffinic hydrocarbons in urea concentrate was determined in diesel fraction. The results of the investigation show that due to low content of sulfur, tar- asphaltenic compounds and high yield of light fractions the Manavi oil can be recognized as a high quality paraffinic type of oil. Physical and chemical characteristics, chemical nature and high yield of light fractions outline a good perspective for usage of Manavi deposit oil as a raw material for production of commodity petroleum products like high quality organic solvents, aviation and diesel fuels and various petroleum oils.